The globalization of markets and regional integration - Paul J. J. Welfens (Intereconomics, 1989)
The 1980s have witnessed the globalization of markets and an intensified international competition. The rise of the newly industrializing countries and the growth of multinational enterprises—developing parallely to foreign direct investments—have contributed considerably to this trend. However, there are factors suggesting that the intensification of market competition might be only a transitory phenomenon.
Keywords: 330; International Competition